Steel sheet having excellent toughness, ductility and strength, and manufacturing method thereof
By using continuous annealing method to process the hot-rolled steel plates in the steel plate manufacturing process, the problems of poor cold-rolled steel plates and degraded mechanical properties are solved, and the high ductility, high strength and good cold-rolling performance of the steel plates are achieved.
Patent Information
- Application Number
- JP2025005978
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2017-12-19
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, when manufacturing high-cold rolling and high-tough steel plates, the hardness of the hot-rolled steel plates is too high before cold rolling, resulting in poor cold rolling performance. Although the batch annealing method can reduce hardness, it will lead to the final mechanical properties of the steel plates, especially the ductility and strength, and the toughness of the hot-rolled steel plates are insufficient, and tape damage is prone to occur.
The hot-rolled steel plate is processed using a continuous annealing method. The specific steps include heat treatment between 1150°C and 1300°C, and final rolling between 800°C and 1250°C after hot rolling. The cooling rate is controlled between 1°C/sec to 150°C/sec, and winding is completed below 650°C, and continuous annealing is performed between 650°C and 700°C, controlling the annealing time between 3 seconds and 3600 seconds, then cooling to room temperature, and finally cold rolling and heat treatment are performed to obtain steel plates with high mechanical properties.
Through the continuous annealing method, the cold rolling performance and toughness of hot-rolled steel plates can be significantly improved, ensuring that the steel plate has high ductility and high strength after cold rolling and heat treatment, while avoiding the mechanical performance degradation and belt damage caused by batch annealing.
Smart Images

Figure 2025063203000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing hot rolled and annealed steel sheet suitable for producing cold rolled and heat treated steel sheet having high cold rollability and toughness with a high combination of ductility and strength, and to the hot rolled and annealed steel sheet produced by this method.
[0002] The present invention relates to a method for producing a cold rolled and heat treated steel sheet having a high combination of ductility and strength, and to the cold rolled and heat treated steel sheet obtained by this method. [Background technology]
[0003] In particular, in the automotive industry, there is a continuous demand for lighter vehicles to improve fuel efficiency in the interest of protecting the global environment, and for improved safety through the use of steels with high tensile strength, which can in fact be used to manufacture parts with a smaller thickness while still guaranteeing the same or improved safety levels.
[0004] To this end, steels have been proposed that contain small alloying elements that simultaneously provide hardening through precipitation and refinement of grain size. Following the development of such steels, higher strength steels, called advanced high strength steels, have been developed that retain a good level of strength and good cold formability.
[0005] With the aim of obtaining even higher tensile strength levels, steels have been developed that exhibit TRIP (transformation induced plasticity) behavior with a highly favorable combination of properties (tensile strength / deformability). These properties are associated with the structure of such steels, which consists of a ferritic matrix containing bainite and retained austenite. The retained austenite is stabilized by the addition of silicon or aluminum, which elements delay the precipitation of carbides in the austenite and in the bainite. The presence of the retained austenite gives the undeformed sheet a high ductility. Under the effect of subsequent deformation, for example when stressed uniaxially, the retained austenite in parts made of TRIP steels is gradually transformed into martensite, which results in a substantial hardening and a delayed appearance of necking.
[0006] To achieve an improved combination of strength and ductility, it has further been proposed to produce the plate by the so-called "quench and carbon enrich" method, where the plate is annealed in the austenite or intercritical domain, cooled to a quenching temperature below the Ms transformation point, and then heated to the carbon enrichment temperature and maintained at this temperature for a predefined time. The resulting steel plate has a structure containing martensite and retained austenite, and optionally bainite and / or ferrite. The retained austenite has a high C content due to carbon enrichment from the martensite during carbon enrichment, and the martensite contains a low percentage of carbides.
[0007] All these steel plates exhibit a good balance of resistance and ductility.
[0008] However, new challenges arise with regard to the production of such plates. In particular, the production process of such steel plates generally involves casting a semi-finished steel product, hot rolling the semi-finished product to produce a hot rolled steel plate, and then coiling the hot rolled steel plate, prior to the heat treatment that imparts the final properties to the steel. The hot rolled steel plate is then cold rolled to the desired thickness and subjected to a heat treatment selected according to the desired final structure and properties to obtain the cold rolled and heat treated steel plate.
[0009] Due to the composition of these steels, a high level of resistance is reached throughout the manufacturing process. In particular, hot-rolled steel sheets exhibit a high hardness before cold rolling that impairs their cold rollability. As a result, the range of available sizes of cold-rolled sheets is narrowed.
[0010] To solve this problem, it has been proposed to batch anneal the hot rolled steel sheet prior to cold rolling at a temperature generally comprised between 500° C. and 700° C. for several hours.
[0011] Batch annealing actually results in a reduction in the hardness of the hot rolled steel sheet, thus improving its cold rollability.
[0012] However, this solution is not entirely satisfactory.
[0013] Indeed, batch annealing treatments generally result in a deterioration of the final properties of the steel, in particular its ductility and strength.
[0014] Also, hot rolled steel sheets exhibit insufficient toughness after batch annealing, which may lead to band fracture during further processing. Summary of the Invention [Problem to be solved by the invention]
[0015] Therefore, an object of the present invention is to provide a hot-rolled steel sheet that is suitable for producing cold-rolled and heat-treated steel sheets having high mechanical properties, particularly a high combination of ductility and strength, while having improved cold-rollability and toughness, and a manufacturing method thereof.
[0016] It is also an object of the present invention to provide a cold rolled and heat treated steel sheet, and a method for its manufacture, which has an improved combination of mechanical properties compared to a similar steel sheet manufactured by a process which includes a batch annealing treatment prior to cold rolling. [Means for solving the problem]
[0017] For this purpose, the present invention comprises the following steps: - in percent by weight, 0.1%≦C≦0.4% 3.5%≦Mn≦8.0% 0.1%≦Si≦1.5% Al≦3% Mo≦0.5% Cr≦1% Nb≦0.1% Ti≦0.1% V≦0.2% B≦0.004% 0.002%≦N≦0.013% S≦0.003% P≦0.015% with the balance being iron and inevitable impurities resulting from smelting, to obtain a semi-finished steel product; - The temperature T of the steel semi-finished product is between 1150℃ and 1300℃. reheat reheating the mixture to - A process of hot rolling the reheated semi-finished product at a temperature between 800 ° C and 1250 ° C, and the final rolling temperature T FRT is 800°C or higher, thereby obtaining a hot-rolled steel sheet; - Hot-rolled steel sheet is cooled at a rate V between 1℃ / sec and 150℃ / sec. c1 The coiling temperature T is 650℃ or less. coil The hot-rolled steel sheet is then cooled to the coiling temperature T coil Then, the process of winding the - T ICAmin ~T ICAmax Continuous annealing temperature T ICA A process for continuously annealing a hot-rolled steel sheet, comprising: ICAmin = 650℃, T ICAmax is the temperature at which 30% austenite is generated during heating, and hot-rolled steel sheets are annealed at the continuous annealing temperature T ICA The continuous annealing time t is between 3 seconds and 3600 seconds. ICA and then - cooling the hot-rolled steel sheet to room temperature, the hot-rolled steel sheet being cooled at an average cooling rate V of at least 1 ° C / s between 600 and 350 ° C. ICA thereby obtaining a hot rolled and annealed steel sheet. - A process of cold rolling the hot rolled and annealed steel sheet with a cold rolling reduction ratio of between 30% and 70%, thereby obtaining a cold rolled steel sheet. The present invention relates to a method for manufacturing a steel sheet, including
[0018] Preferably, the hot rolled and annealed steel sheet has a surface fraction of - ferrite (the ferrite grains have an average size of up to 3 μm), - up to 30% austenite, - max. 8% fresh martensite, and - Cementite with an average Mn content below 25% The organization consists of the following:
[0019] Generally, hot rolled and annealed steel sheets have a Vickers hardness of less than 400 HV.
[0020] Preferably, the hot rolled and annealed steel sheet has a thermal resistance of at least 50 J / cm at 20°C. 2 has a Charpy energy of
[0021] Preferably, the method further comprises the step of pickling the hot rolled steel sheet between coiling and continuous annealing and / or after continuous annealing.
[0022] Preferably, the continuous annealing time t ICA is between 200 and 3600 seconds.
[0023] Preferably, the method further comprises, after cold rolling, - Cold-rolled steel sheets are annealed at temperatures T between 650 and 1000°C. anneal and - Cold-rolled steel sheet is annealed at temperature T anneal Annealing time t is between 30 seconds and 10 minutes. anneal Hold for This includes:
[0024] In the first embodiment, the annealing temperature T anneal is TICAmin Included between ~Ae3.
[0025] In the second embodiment, the annealing temperature T anneal is included between Ae3 and 1000°C.
[0026] According to one embodiment, the method further comprises subjecting the cold rolled steel sheet to an annealing temperature T anneal From room temperature, the cooling rate V is between 1℃ / sec and 70℃ / sec c2 to obtain a cold rolled and heat treated steel sheet.
[0027] In another embodiment, the method further comprises subjecting the cold rolled steel sheet to an annealing temperature T anneal After holding at , the following successive steps are performed: - Cold-rolled steel sheet is annealed at temperature T anneal The holding temperature T is between 350℃ and 550℃. H Cooling rates V range from 1°C / sec to 70°C / sec c2 cooling with - Retention time t between 10 seconds and 500 seconds H Cold rolled steel sheet is kept at temperature T H and then - Holding temperature T of cold rolled steel sheet H Cooling rate V from 1℃ / sec to room temperature is between 1℃ / sec and 70℃ / sec c3 and cooling the steel sheet to obtain a cold-rolled and heat-treated steel sheet. Includes.
[0028] Preferably, the method comprises a tempering temperature T comprised between 170 and 450 ° C. T The tempering time t is between 10 seconds and 1200 seconds. T The method further comprises the step of tempering the cold rolled and heat treated steel sheet during the process.
[0029] Preferably, the method further comprises the step of coating the cold rolled and heat treated steel sheet with Zn or a Zn alloy, or Al or an Al alloy.
[0030] In another embodiment, the method further comprises the steps of: - The heated cold-rolled steel sheet is annealed at a temperature T anneal A cooling rate V high enough to avoid the formation of ferrite and pearlite during cooling to a quenching temperature QT comprised between Mf+20℃ and Ms-20℃ c4 A process of hardening with - Cold-rolled steel sheet is quenched at a carbon concentration temperature T between 350℃ and 500℃. P The cold-rolled steel sheet is then reheated to the carbon concentration temperature T P The carbon concentration time t between 3 and 1000 seconds P maintaining the temperature for a period of time; - cooling the cold rolled steel sheet to room temperature to obtain a cold rolled and heat treated steel sheet; Includes.
[0031] In the first variant of this embodiment, the annealing temperature T anneal During annealing, the surface fraction of cold-rolled steel sheet is - Between 10% and 45% ferrite, - austenite, and - Maximum 0.3% cementite (cementite grains have an average size, if any, smaller than 50 nm). It is as if we had an organization consisting of the above.
[0032] In the second variant of this embodiment, the annealing temperature T anneal is higher than Ae3, and cold-rolled steel sheets have - austenite, and - Maximum 0.3% cementite (cementite grains have an average size, if any, smaller than 50 nm). The organization consists of the following:
[0033] The cold-rolled steel sheet is heated to a carbon concentration temperature T P After being held at this temperature, the cold rolled steel sheet can be immediately cooled to room temperature.
[0034] In a variant, the carbon enrichment temperature T PBetween holding the cold rolled steel sheet at 0° C. and cooling the cold rolled steel sheet to room temperature, the cold rolled steel sheet is hot-dip galvanized in the bath.
[0035] Preferably, the Si content in this composition is at most 1.4%.
[0036] The present invention also provides, in weight percent: 0.1%≦C≦0.4% 3.5%≦Mn≦8.0% 0.1%≦Si≦1.5% Al≦3% Mo≦0.5% Cr≦1% Nb≦0.1% Ti≦0.1% V≦0.2% B≦0.004% 0.002%≦N≦0.013% S≦0.003% P≦0.015% and the balance being iron and unavoidable impurities resulting from smelting, and the cold rolled steel plate is made from a steel having a composition comprising, in terms of surface fraction: - Between 8 and 50% retained austenite, - maximum 80% intercritical ferrite (ferrite grains have an average size of maximum 1.5 μm, if any); - maximum 1% cementite (cementite grains have an average size, if any, of less than 50 nm); - Martensite and / or Bainite The present invention also relates to a cold-rolled and heat-treated steel sheet having a structure consisting of:
[0037] In one embodiment, the structure contains at least 10% intercritical ferrite in the surface fraction.
[0038] In another embodiment, the tissue has a surface fraction of: - Between 8 and 50% retained austenite, - maximum 1% cementite (cementite grains have an average size, if any, of less than 50 nm); - Martensite and / or Bainite It consists of:
[0039] According to one embodiment, the martensite consists of tempered martensite and / or fresh martensite.
[0040] In a first variant of this embodiment, the texture has a surface fraction of: - retained austenite having an average C content of at least 0.4% and an average Mn content of at least 1.3*Mn%, between 8% and 50%, where Mn% indicates the average Mn content in the steel composition; - ferritic transformation interval between 40% and 80%, - max. 15% martensite and / or bainite, and - Maximum 0.3% cementite (cementite grains have an average size, if any, less than 50 nm). It consists of:
[0041] In a second variation of this embodiment, the texture has a surface fraction of: - retained austenite with an average C content of at least 0.4%, between 8% and 30%; - between 70% and 92% martensite and / or bainite, and - Maximum 1% cementite (cementite grains have an average size, if any, less than 50 nm). It consists of:
[0042] In another embodiment, the tissue has a surface fraction of: - up to 45% intercritical ferrite, - Between 8% and 30% retained austenite, - carbon enriched martensite, - max. 8% fresh martensite, and - Maximum 1% cementite (cementite grains have an average size, if any, less than 50 nm). It consists of:
[0043] In a first variant of this embodiment, the texture has a surface fraction of: - ferritic transformation interval between 10% and 45%, - Between 8% and 30% retained austenite, - carbon enriched martensite, - max. 8% fresh martensite, and - Maximum 0.3% cementite (cementite grains have an average size, if any, less than 50 nm). It consists of:
[0044] In a second variation of this embodiment, the texture has a surface fraction of: - Between 8% and 30% retained austenite, - carbon enriched martensite, - max. 8% fresh martensite, and - Maximum 1% cementite (cementite grains have an average size, if any, less than 50 nm). It consists of:
[0045] Preferably, the Si content in the composition is at most 1.4%.
[0046] The invention is described in detail below and illustrated by way of example, without introducing any limitation, with reference to the accompanying figures. [Brief description of the drawings]
[0047] [Figure 1] 1 is a photomicrograph showing the structure of a comparative hot-rolled and batch-annealed steel sheet. [Diagram 2] 1 is a micrograph showing the structure of hot-rolled steel that has been subjected to continuous annealing according to the present invention. [Diagram 3] 1 is a graph comparing the mechanical properties of cold rolled and heat treated steel sheets produced from either hot rolled and batch annealed steel sheets or hot rolled and continuous steel sheets. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0048] According to the present invention, the carbon content is between 0.1% and 0.4%. Carbon is an element that stabilizes austenite. Below 0.1%, it is difficult to achieve a high level of tensile strength. If the carbon content exceeds 0.4%, the cold rolling property is reduced and the weldability is deteriorated. Preferably, the carbon content is between 0.1% and 0.2%.
[0049] The manganese content is comprised between 3.5 and 8.0%. Manganese provides a solid solution hardening and a refining effect on the microstructure. Manganese therefore contributes to an increase in tensile strength. At contents above 3.5%, Mn is used to provide significant stabilization of austenite in the microstructure throughout the entire manufacturing process and in the final structure. In particular, when the Mn content exceeds 3.5%, a final structure of the cold-rolled and heat-treated steel sheet containing at least 8% retained austenite can be achieved. Furthermore, due to the stabilization of the retained austenite by Mn, high ductility is obtained. At contents above 8.0%, the weldability is poor and at the same time segregations and inclusions deteriorate the damage properties.
[0050] Silicon is very efficient in increasing strength through solid solution and stabilizing austenite. Moreover, silicon retards the formation of cementite on cooling by significantly retarding the precipitation of carbides. This is due to the fact that the solubility of silicon in cementite is very low and Si increases the activity of carbon in austenite. Thus, the formation of cementite is preceded by a step of expelling Si at the interface. Thus, the enrichment of austenite by carbon leads to its stabilization at room temperature.
[0051] For this reason, the Si content is at least 0.1%. However, the Si content is limited to 1.5%, because above this value the rolling load becomes too large, making the hot rolling process difficult. Also, the cold rolling properties deteriorate. In addition, too high a content leads to the formation of silicon oxide on the surface, which impairs the coatability of the steel.
[0052] The Si content is preferably at most 1.4%. In fact, a Si content of at most 1.4% can lead to the formation of fayalite (Fe olivine) during hot rolling. 2 SiO 4 The occurrence of red scale (also called tiger stripes) caused by the presence of .
[0053] Aluminum is a very effective element for deoxidizing steel in the liquid phase during refining. Preferably, the Al content is greater than or equal to 0.003% to obtain sufficient deoxidation of the liquid steel.
[0054] In addition, like Si, Al stabilizes the retained austenite and delays the formation of cementite on cooling, but the Al content must be below 3% to avoid inclusion formation, avoid oxidation problems, and ensure the hardenability of the material.
[0055] The steel of the invention may contain at least one element chosen among molybdenum and chromium.
[0056] Molybdenum increases hardenability, stabilizes retained austenite, and reduces center segregation that can result from manganese content and is detrimental to formability. Above 0.5%, Mo may form too many carbides, which is detrimental to ductility.
[0057] However, even if no Mo is added, the steel may contain at least 0.001% Mo as an impurity. If Mo is added, the Mo content is generally at least 0.05%.
[0058] Chromium improves the hardenability of steel and contributes to achieving high tensile strength. A maximum of 1% chromium is permitted. In fact, above 1%, a saturation effect is observed and adding chromium becomes both useless and expensive. If chromium is added, its content is generally at least 0.01%. In the absence of voluntary additions of chromium, chromium contents may be present as an impurity at levels as low as 0.001%.
[0059] Microalloying elements such as titanium, niobium and vanadium can be added to obtain additional precipitation hardening, with contents up to 0.1% Ti, up to 0.1% Nb and up to 0.2% V. In particular, titanium and niobium are used to control grain size during solidification.
[0060] If Nb is added, its content is preferably at least 0.01%. Above 0.1%, a saturation effect is obtained, and adding more than 0.1% Nb is both useless and expensive.
[0061] When Ti is added, its content is preferably at least 0.015%. When the Ti content is comprised between 0.015% and 0.1%, precipitation occurs at very high temperatures in the form of TiN, and then at lower temperatures in the form of fine TiC, resulting in hardening. Furthermore, when titanium is added in addition to boron, titanium prevents the combination of boron with nitrogen, and nitrogen combines with titanium. Therefore, when boron is added, the titanium content is preferably higher than 3.42N. However, the Ti content should remain below 0.1% in order to avoid the precipitation of coarse TiN precipitates, which increases the hardness of the hot-rolled and cold-rolled steel sheets during the manufacturing process.
[0062] Optionally, the steel composition contains boron to increase the hardenability of the steel. If B is added, its content is higher than 0.0002%, preferably higher than 0.0005%, with a maximum of 0.004%. Indeed, beyond such limits a saturation level is expected with respect to hardenability.
[0063] Generally, sulfur, phosphorus and nitrogen are present in the steel composition as impurities.
[0064] The nitrogen content is generally at least 0.002%. To prevent the precipitation of coarse TiN and / or AlN precipitates from degrading the ductility, the nitrogen content should be a maximum of 0.013%.
[0065] As regards sulfur, at contents above 0.003%, the presence of excess sulfides such as MnS reduces ductility, especially hole expansion tests show lower values in the presence of such sulfides.
[0066] Phosphorus is a hardening element in solid solution, but it also reduces spot weldability and hot ductility due to its tendency to segregate, especially at grain boundaries, or to co-segregate with manganese. For these reasons, its content must be limited to 0.015% in order to obtain good spot weldability.
[0067] The remainder is made up of iron and unavoidable impurities, which may include up to 0.03% Cu and up to 0.03% Ni.
[0068] The method according to the invention aims to provide a hot rolled and annealed steel sheet having high cold rollability together with high toughness and a high combination of ductility and strength, suitable for the production of cold rolled and heat treated steel sheet.
[0069] The method according to the invention is also aimed at the production of such cold-rolled and heat-treated steel sheets.
[0070] The inventors have investigated the problems of poor toughness of hot rolled and batch annealed steel plates, and the degradation of mechanical properties of cold rolled and heat treated steel plates produced from such hot rolled and batch annealed steel plates compared to steel plates that would not have been subjected to annealing, and have found that these problems arise from four main factors.
[0071] In particular, the inventors have discovered that batch annealing results in the formation of coarse cementite that is highly enriched in manganese and is therefore highly stabilized in the hot rolled and batch annealed steel sheet. The inventors have further discovered that the cementite thus stabilized does not completely dissolve during the subsequent standard heat treatment of the cold rolled steel sheet. As a result, part of the Mn in the steel remains trapped in the cementite, thus suppressing its effect on the strength and ductility of the steel.
[0072] The inventors further discovered that batch annealing also coarsens the structure of the hot rolled and batch annealed steel sheet, which results in a coarsened final structure and poor mechanical properties in the cold rolled and heat treated steel sheet.
[0073] Furthermore, the inventors have discovered that minor alloying elements that may be included in the steel composition, particularly Nb, precipitate early during batch annealing as coarse precipitates that do not harden the steel, and as a result are unavailable for precipitation hardening during subsequent heat treatment of the cold rolled steel sheet.
[0074] Finally, the inventors have found that batch annealing, performed at certain temperatures and for certain times, induces temper embrittlement, resulting in poor toughness of hot rolled and batch annealed steel sheet.
[0075] To solve these problems, the inventors conducted experiments by increasing the batch annealing temperature above the Ae1 transformation point of the steel.
[0076] However, the inventors have found that the use of higher batch annealing temperatures, although it limits the formation of Mn-rich cementite, leads to coarsening of the microstructure, which is detrimental to the final properties of the cold rolled and heat treated steel sheet.
[0077] From these findings, the present inventors have concluded that the hot-rolled steel sheet has the following properties: - ferrite with an average ferrite grain size of up to 3 μm; - up to 30% austenite, - max. 8% fresh martensite, and - Cementite with an average Mn content of less than 25% It has been discovered that if the steel plate is annealed to have a microstructure containing
[0078] A fresh martensite fraction of up to 8% makes it possible to achieve high toughness in hot-rolled and annealed steel sheets.
[0079] In particular, the inventors conducted experiments in which hot-rolled steel sheets made of several different steel compositions were subjected to various annealing conditions to arrive at the fractions of austenite and fresh martensite that change after cooling to room temperature, and measured the Charpy energy at 20°C of the steel sheets thus obtained.
[0080] Based on these experiments, the inventors found that the Charpy energy is an increasing function of the annealing temperature and a decreasing function of the fresh martensite fraction. Furthermore, the inventors found that the Charpy energy is at least 50 J / cm at 20° C. when the hot rolled and annealed steel sheet has a fresh martensite fraction of up to 8%. 2 It has been found that a high Charpy energy of
[0081] Furthermore, cementite with an average Mn content lower than 25% means that cementite dissolution is easier during the final heat treatment of the cold rolled steel sheet, which improves ductility and strength during further processing steps. In contrast, cementite with an average Mn content higher than 25% will result in a decrease in the mechanical properties of the cold rolled and heat treated steel sheet produced from said hot rolled and annealed steel sheet.
[0082] In addition, having an average ferrite grain size of up to 3 μm makes it possible to produce cold rolled and heat treated steels with a very fine microstructure, increasing their mechanical properties.
[0083] The inventors have further found that with the above microstructure it is possible to achieve a hardness of the hot rolled and annealed steel sheet below 400HV, which ensures satisfactory cold rollability of the hot rolled and annealed steel sheet.
[0084] The inventors have determined that the microstructure and these properties of the hot rolled and annealed steel sheet are affected by the minimum continuous annealing temperature TICAmin = The maximum continuous annealing temperature T at which 30% austenite is formed when heated from 650°C ICAmax Continuous annealing temperature T ICA It has been found that this can be achieved by performing continuous annealing for a time included in the range of 3 seconds to 3600 seconds, and then cooling the hot-rolled steel sheet under specific cooling conditions.
[0085] In particular, the inventors have found that the high continuous annealing temperature T ICA Therefore, it has been found that an annealing time of up to 3600 seconds is sufficient to achieve sufficient tempering of the structure, thereby improving the cold rollability of the hot-rolled and annealed steel sheet, while avoiding coarsening of the structure.
[0086] Annealing the plate at temperatures above 650°C also allows softening of the hot rolled plate, limits Mn enrichment in the cementite grains to less than 25%, limits precipitation of micro-alloying elements, if any, and prevents coarsening of such precipitates, thereby preserving the influence of C, Mn and micro-alloying elements on the final mechanical properties, and limits the segregation of brittle impurities such as P at grain boundaries.
[0087] The manufacturing method will now be described in more detail.
[0088] The method of producing the steel of the present invention comprises casting a steel of the present chemical composition.
[0089] The cast steel is heated to a temperature T between 1150°C and 1300°C. reheat It is reheated until
[0090] Slab reheat temperature T reheat If the rolling temperature is less than 1150° C., the rolling load becomes too large, making the hot rolling process difficult.
[0091] Above 1300°C, oxidation becomes very severe, leading to scale loss and surface deterioration.
[0092] The reheated slabs are hot rolled at temperatures between 1250 °C and 800 °C, with the last hot rolling pass at a final rolling temperature T above 800 °C. FRT It is held.
[0093] Final rolling temperature T FRT If the temperature is less than 800° C., the hot workability decreases.
[0094] After hot rolling, the steel is cooled at a rate V between 1℃ / s and 150℃ / s. c1 The coiling temperature T is 650℃ or less. coil Below 1°C / s a microstructure that is too coarse will be produced and the final mechanical properties will be poor. Above 150°C / s the cooling process is difficult to control.
[0095] Winding temperature T coil The coiling temperature must be below 650°C. If the coiling temperature exceeds 650°C, deep intergranular oxide will form under the scale, leading to deterioration of the surface properties.
[0096] After coiling, the hot-rolled steel sheet is preferably pickled.
[0097] The hot-rolled steel sheet is then continuously annealed, i.e. the uncoiled hot-rolled steel sheet is subjected to a heat treatment by moving continuously through a furnace.
[0098] Hot-rolled steel sheets are annealed at a minimum continuous annealing temperature T ICAmin = The maximum continuous annealing temperature T at which 30% austenite is formed when heated from 650°C ICAmax Continuous annealing temperature T ICA and continuous annealing for a time period comprised between 3 seconds and 3600 seconds.
[0099] Under these conditions, the microstructure of the steel created during continuous annealing is - Ferrite, - less than 30% austenite, - Cementite with an average Mn content of less than 25% It consists of:
[0100] If the continuous annealing temperature is lower than 650°C, the softening caused by microstructural recovery during the continuous annealing process is insufficient, so the hardness of the hot-rolled and annealed steel plate exceeds 400HV. Also, a continuous annealing temperature lower than 650°C will enhance the segregation of embrittling elements such as P at the grain boundaries, resulting in insufficient toughness value, which is critical for the further processing of the steel plate.
[0101] Continuous annealing temperature is T ICAmax If it is higher, too high austenite fraction will occur during continuous annealing, which may result in insufficient stabilization of austenite and the formation of more than 8% fresh martensite on cooling.
[0102] If the continuous annealing time is shorter than 3 seconds, the hardness of the hot-rolled and annealed steel sheet will be too high, especially higher than 400HV, so that its cold rollability will be unsatisfactory. It is preferable that the continuous annealing time is at least 200 seconds.
[0103] If the continuous annealing time is longer than 3600 seconds, the microstructure becomes coarse, in particular the ferrite grains have an average size of more than 3 μm.The continuous annealing time is preferably a maximum of 500 seconds.
[0104] The austenite that can be produced during annealing is rich in carbon and manganese, in particular having an average Mn content of at least 1.3*Mn% (Mn% indicates the Mn content of the steel) and an average C content of at least 0.4%.
[0105] Thus, the austenite is highly stabilized.
[0106] Next, the hot-rolled steel sheet is annealed at a temperature T ICA From this temperature, the material is cooled to room temperature, where the average cooling rate between 600°C and 350°C is V ICA is at least 1°C / sec. Under these conditions, temper embrittlement is limited.
[0107] If the cooling rate between 600° C. and 350° C. is less than 1° C. / sec, segregation that increases temper embrittlement occurs in the hot-rolled and annealed steel sheet, and the cold rollability is therefore unsatisfactory.
[0108] The hot-rolled and annealed steel sheet thus obtained is - Ferrite, - up to 30% austenite, - max. 8% fresh martensite, - Cementite with an average Mn content of less than 25% The organization consists of the following:
[0109] Due to the stabilization of austenite by Mn, a maximum fresh martensite fraction of 8% is achieved, so that the austenite does not transform into fresh martensite on cooling, or only to a small extent.
[0110] The retained austenite of the hot rolled and annealed steel sheet has an average Mn content of at least 1.3*Mn%, where Mn% denotes the Mn content of the steel, and an average C content of at least 0.4%.
[0111] A tempering treatment is optionally performed to further limit the fraction of fresh martensite.
[0112] Moreover, the ferrite grains have an average size of up to 3 μm. In fact, continuous annealing, which is carried out for a relatively short time compared to batch annealing, does not result in coarsening of the structure and therefore makes it possible to achieve hot-rolled and annealed sheets with a very fine structure.
[0113] At this stage, the hot rolled and annealed steel sheet has improved cold rollability and toughness compared to the hot rolled steel sheet before annealing, and is suitable for producing cold rolled and heat treated steel sheets with high mechanical properties, especially high ductility and strength.
[0114] In particular, the hot rolled and annealed sheet has a Vickers hardness below 400 HV and therefore has very good cold rollability.
[0115] In addition, hot-rolled and annealed steel sheets have a resistance of at least 50 J / cm at 20°C. 2 The hot rolled and annealed steel sheet therefore has a very good workability and the risk of band breakage during further processing is greatly reduced compared to a hot rolled steel sheet that would have been batch annealed. The inventors have also discovered that not only is the Charpy energy of the hot rolled and annealed steel sheet higher than that of the hot rolled and batch annealed steel sheet, but that the Charpy energy of the hot rolled and annealed steel sheet is generally higher than that of the hot rolled steel sheet produced therefrom.
[0116] After cooling to room temperature, the hot rolled and annealed steel sheet is optionally pickled. However, this step may be omitted. In fact, due to the short duration of the continuous annealing, no or very little internal oxidation occurs during the continuous annealing. If pickling was not performed between hot rolling and continuous annealing, it is preferable to pickle the hot rolled and annealed steel sheet at this stage.
[0117] Then, the hot rolled steel sheet is cold rolled with a cold rolling reduction ratio of 30% to 70% to obtain a cold rolled steel sheet. If the reduction ratio is less than 30%, it is not favorable for recrystallization during the subsequent heat treatment, and the ductility of the cold rolled steel sheet after heat treatment may be impaired. If the reduction ratio exceeds 70%, there is a risk of edge cracking during cold rolling.
[0118] The cold rolled steel sheet is then heat treated in a continuous annealing line to produce a cold rolled and heat treated steel sheet.
[0119] The heat treatment performed on the cold rolled steel sheet is selected depending on the final mechanical properties desired.
[0120] In either case, the heat treatment is performed by subjecting the cold-rolled steel sheet to an annealing temperature T anneal The cold-rolled steel sheet is heated to annealing temperature T annealAnnealing time t is between 30 seconds and 10 minutes. anneal The method includes holding the substrate for a period of time.
[0121] Furthermore, the annealing temperature T anneal is such that the structure produced during annealing contains at least 8% austenite.
[0122] If the annealing temperature is lower than 650°C, cementite will form in the structure during annealing, resulting in deterioration of the mechanical properties of the cold-rolled and heat-treated steel sheet.
[0123] In order to limit the coarsening of the austenite grains, the annealing temperature T anneal The maximum temperature is 1000°C.
[0124] Annealing temperature T anneal The reheating rate Vr up to is preferably comprised between 1° C. / s and 200° C. / s.
[0125] According to a first embodiment, the annealing is an intercritical annealing, the annealing temperature T anneal is lower than Ae3 and the structure produced during annealing is such that it contains at least 8% austenite.
[0126] According to the second embodiment, in order to obtain a structure consisting of austenite and at most 1% cementite during annealing, the annealing temperature T anneal is greater than or equal to Ae3.
[0127] In a first embodiment, at the end of the hold at the annealing temperature, the austenite has a C content of at least 0.4% and an average Mn content of at least 1.3*Mn%.
[0128] Next, the cold-rolled and annealed steel sheet is directly, i.e., annealed at a temperature T anneal and room temperature without, or indirectly, i.e. with, a holding, tempering and / or reheating step between the steel sheet and room temperature, to obtain a cold-rolled and heat-treated steel sheet.
[0129] In either case, the cold-rolled and heat-treated steel sheet is - Between 8% and 50% retained austenite, martensite (which may include fresh martensite and / or carbon enriched or tempered martensite, and optionally bainite); - up to 80% intercritical ferrite, and - Maximum 1% cementite The company has an organization (hereinafter referred to as the final organization) that includes the above.
[0130] The retained austenite typically has an average C content of at least 0.4% and an average Mn content of at least 1.3*Mn%.
[0131] Due to the Mn content in cementite of up to 25% in the microstructure of the hot-rolled and annealed steel sheet, the cementite dissolves easily during annealing. Depending on the heat treatment carried out, small amounts of cementite may remain in the final structure. However, the cementite fraction in the final structure remains below 1% in any case. Furthermore, the cementite particles have an average size, if any, of less than 50 nm.
[0132] The martensite may include fresh martensite and carbon enriched or tempered martensite.
[0133] As will be explained in more detail below, the carbon-enriched martensite has an average C content strictly lower than the nominal C content of the steel. This lower C content is due to the carbon enrichment temperature T P This arises from carbon enrichment during storage at .
[0134] In contrast, tempered martensite has an average C content equal to the nominal C content of the steel. Tempered martensite results from the tempering of martensite made by quenching below the Ms temperature of the steel.
[0135] Carbon-enriched martensite can be distinguished from tempered martensite and fresh martensite on sections polished and etched with known reagents, such as Nital reagent, observed by scanning electron microscopy (SEM) and electron backscatter diffraction (EBSD).
[0136] This structure is bainite, especially 100 mm 2 The carbide-free bainite may include less than 100 carbides per surface unit.
[0137] The ferrite fraction depends on the annealing temperature during heat treatment.
[0138] The ferrite, if present in the final structure, is intercritical ferrite.
[0139] Thus, if present, the ferrite is inherited from the structure of the hot-rolled and annealed steel sheet which is subsequently cold-rolled and recrystallized, so that the ferrite has an average grain size of at most 1.5 μm.
[0140] Here, the preferred heat treatment to be performed on the cold rolled steel sheet will be described in more detail.
[0141] In the first preferred heat treatment, the annealing temperature T is lower or higher than Ae3. anneal After holding at , the cold rolled steel sheet is cooled at a rate V between 1℃ / sec and 70℃ / sec. c2 The mixture is cooled to room temperature.
[0142] Cold-rolled steel sheets are cooled at a rate of V c2 or cooled to room temperature at a cooling rate of V c2 The holding temperature T is between 350 and 550°C. H The temperature is then cooled to T HSuch a heat treatment, which facilitates, for example, hot-dip Zn coating, has been shown not to affect the final mechanical properties. H After an optional hold at , a cooling rate V between 1 °C / s and 70 °C / s is applied. c3 The cold rolled steel sheet is cooled to room temperature.
[0143] Optionally, after cooling to room temperature, the temperature T t The tempering time t is between 10 and 1200 seconds. t During this time, the cold rolled and heat treated steel sheet is tempered.
[0144] This treatment allows tempering of the martensite that can be produced during cooling to room temperature after annealing. In this way the hardness of the martensite is reduced and its ductility is improved. Below 170°C the tempering process is not efficient enough. Above 450°C the strength loss is high and the balance between strength and ductility is not further improved.
[0145] The structure of the cold-rolled and heat-treated steel sheet obtained by the first preferred heat treatment has a surface fraction of: - retained austenite with an average C content of at least 0.4%, between 8% and 50%; - up to 80% interphase ferrite, - up to 92% martensite and / or bainite, - Maximum 1% cementite It consists of:
[0146] The martensite comprises tempered martensite and / or fresh martensite.
[0147] This structure is bainite, especially 100 mm 2 The carbide-free bainite may include less than 100 carbides per surface unit.
[0148] The average size of the cementite grains is less than 50 nm.
[0149] The fraction of ferrite and austenite depends on the annealing temperature during heat treatment.
[0150] In a first variant of the first preferred heat treatment, the annealing temperature T anneal is lower than Ae3, and preferably the structure produced during annealing contains 40% to 80% ferrite.
[0151] In this first variant, the final structure preferably has a surface fraction: - 8-50% retained austenite with an average C content of at least 0.4% and an average Mn content of at least 1.3*Mn%, - 40-80% interphase ferritic (ferrite grains have an average size of up to 1.5 μm), - max. 15% martensite (consisting of tempered martensite and / or fresh martensite) and / or bainite, - Maximum 0.3% cementite (cementite grains have an average size, if any, less than 50 nm). Includes.
[0152] In a second variant of the first preferred heat treatment, the annealing temperature is greater than or equal to Ae3.
[0153] In this second variant, the final structure is - 8-30% retained austenite with an average C content of at least 0.4%, - 70% to 92% martensite (consisting of tempered martensite and / or fresh martensite) and / or bainite, - Maximum 1% cementite (cementite grains have an average size, if any, less than 50 nm.) It consists of:
[0154] In a second preferred heat treatment, the cold rolled steel sheet is subjected to a quenching and carbon enrichment treatment.
[0155] For this purpose, the annealing temperature T anneal After being held at this temperature, the cold-rolled steel sheet is annealed at the annealing temperature T anneal A cooling rate V high enough to avoid the formation of ferrite and pearlite during cooling from the quenching temperature QT below the Ms transformation point of austenite c4 It is hardened by.
[0156] Cooling rate V to quenching temperature QT c4 is preferably at least 2° C. / sec.
[0157] During this quenching process, the austenite is partially transformed into martensite.
[0158] The quenching temperature is selected between Mf+20°C and Ms-20°C depending on the desired final structure, in particular the fraction of carbon-enriched martensite and retained austenite desired in the final structure. For each specific composition of steel and each structure, the skilled person knows how to determine the Ms and Mf start and end transformation points of austenite by dilatometry.
[0159] If the quenching temperature QT is lower than Mf+20°C, the carbon-rich martensite fraction in the final structure will be too high, and if the quenching temperature QT is higher than Ms-20°C, the carbon-rich martensite fraction in the final structure will be too low, and high ductility will not be achieved.
[0160] A person skilled in the art knows how to determine the appropriate quenching temperature to obtain the desired structure.
[0161] The cold rolled steel sheet is optionally held at the quenching temperature QT for a holding time tQ comprised between 2 s and 200 s, preferably between 3 s and 7 s, in order to avoid the formation of epsilon carbides in the martensite, which would result in a decrease in the ductility of the steel.
[0162] Next, the cold-rolled steel sheet has a carbon concentration temperature T P It is reheated to the carbon concentration temperature T PThe carbon concentration time t between 3 and 1000 seconds P During this carbon enrichment step, carbon diffuses from martensite to austenite, thereby achieving an enrichment of C in the austenite.
[0163] Carbon enrichment time t P If the temperature is higher than 500° C. or lower than 350° C., the elongation of the final product is not satisfactory.
[0164] Optionally, the cold-rolled steel sheet is hot-dip galvanized, for example in a bath at a temperature up to 480° C. Any type of coating can be used, in particular zinc or a zinc alloy, such as zinc-nickel, zinc-magnesium or zinc-magnesium-aluminium alloy, aluminium or an aluminium alloy, such as aluminium-silicon.
[0165] Immediately after the carbon concentration step, or after the hot-dip galvanizing step if a hot-dip galvanizing step is performed, the cold-rolled steel sheet is cooled to room temperature to obtain a cold-rolled and heat-treated steel sheet. The cooling rate to room temperature is preferably higher than 1°C / sec, and is, for example, between 2°C / sec and 20°C / sec.
[0166] The final structure of the cold-rolled and heat-treated steel sheet obtained by the second preferred heat treatment is mainly determined by the annealing temperature T anneal and depends on the quenching temperature QT.
[0167] However, the structure of the cold-rolled and heat-treated steel sheet thus obtained generally has a surface fraction of: - Between 8% and 30% retained austenite, - up to 45% interphase ferrite, - carbon enriched martensite, - max. 8% fresh martensite, - Maximum 1% cementite It consists of:
[0168] The retained austenite is carbon-rich, in particular having an average C content of at least 0.4%.
[0169] The ferrite, if present, is intercritical ferrite and has an average grain size of up to 1.5 μm.
[0170] The fraction of fresh martensite in the structure is not more than 8%. In fact, a fraction of fresh martensite higher than 8% will impair the hole expansion ratio HER.
[0171] In this second preferred heat treatment, small amounts of cementite may form upon cooling from the annealing temperature and upon carbon enrichment, but the fraction of cementite in the final structure remains below 1% in any case, and the average size of the cementite particles in the final structure remains below 50 nm.
[0172] In a first variant of the second preferred embodiment, the annealing temperature T anneal is the surface fraction of cold rolled steel sheet during annealing. - Between 10% and 45% ferrite, - austenite, and - Maximum 0.3% cementite (cementite grains have an average size, if any, less than 50 nm). It is as if we had an organization consisting of the above.
[0173] In this first variant, the final structure preferably has a surface fraction of: - 10-45% intercritical ferrite with an average grain size of up to 1.5 μm, - Between 8% and 30% retained austenite, - carbon enriched martensite, - max. 8% fresh martensite, and - Maximum 0.3% cementite (cementite grains have an average size, if any, less than 50 nm). Includes.
[0174] The retained austenite is rich in Mn and C. In particular, the average C content in the retained austenite is at least 0.4% and the average Mn content in the retained austenite is at least 1.3*Mn%.
[0175] In a second variant of the second preferred embodiment, the annealing temperature T anneal is equal to or greater than Ae3, so that the cold-rolled steel sheet has a structure consisting of austenite and a maximum of 0.3% cementite when annealed.
[0176] In this second variant, the quenching temperature QT is preferably selected so as to obtain, immediately after quenching, a structure consisting of between at most 8% and 30% austenite, at most 92% martensite and at most 1% cementite.
[0177] In this second variant, the final structure is a surface fraction: - Between 8% and 30% retained austenite, - carbon enriched martensite, - max. 8% fresh martensite, and - Maximum 1% cementite (cementite grains have an average size, if any, less than 50 nm). It consists of:
[0178] The retained austenite is rich in C, and the average C content in the retained austenite is at least 0.4%.
[0179] The above microstructural characteristics are determined by observing the microstructure using, for example, a scanning electron microscope equipped with a field emission gun ("FEG-SEM") at magnifications of greater than 5000x, coupled to an electron backscatter diffraction ("EBSD") instrument and a transmission electron microscope (TEM). EXAMPLES
[0180] As examples and comparisons, plates were produced made from steel compositions according to Table I, the contents of which are expressed in percentages by weight.
[0181] [Table 1]
[0182] In the first experiment, steels I1, I2, I3, I6 and I7 were cast to obtain ingots. The ingots were heated to a temperature T reheat The steel was reheated at 400° C., scale was removed, and hot rolled at a temperature higher than Ar3 to obtain hot rolled steel.
[0183] Next, the hot-rolled steel is cooled at a cooling rate V between 1℃ / sec and 150℃. c1 The winding temperature T coil Cool to this temperature T coil and reeled it in.
[0184] A portion of the hot-rolled steel is then annealed either continuously or for an annealing time t A During this time, the annealing temperature T A Then, the average cooling rate V between 600℃ and 350℃ was ICA The mixture was cooled to room temperature.
[0185] The manufacturing conditions of the hot rolled and annealed steel sheets are reported in Table 2 below, along with the austenite fraction generated during annealing.
[0186] [Table 2] TIFF2025063203000004.tif81170
[0187] In Table 2, underlined values are not according to the invention and "nd" means "not determined."
[0188] The inventors investigated the microstructure of the thus obtained hot rolled and optionally annealed steel sheets by a scanning electron microscope equipped with a field emission gun ("FEG-SEM") at a magnification of 5000x, coupled to an electron backscatter diffraction ("EBSD") device and a transmission electron microscope (TEM).
[0189] In particular, the inventors measured the ferrite grain size, the surface fraction of fresh martensite (FM), the surface fraction of austenite (RA) and the average Mn content in cementite (Mn% in cementite).
[0190] The inventors further measured the Charpy energy and Vickers hardness of the hot rolled steel sheets at 20° C. The microstructural characteristics and mechanical properties are reported in Table 3 below.
[0191] [Table 3] TIFF2025063203000006.tif83170
[0192] In this table, nd means "not determined." Underlined values are not according to the present invention.
[0193] These experiments show that the desired microstructure and desired mechanical properties of the hot rolled and annealed steel sheet are achieved only if the hot rolled steel sheet is annealed under the conditions of the present invention.
[0194] In contrast, Examples I1A, I2A, I3A, I6A and I7A did not undergo any annealing.
[0195] As a result, their hardness is higher than 400 HV, so that the cold rollability of these hot rolled steel sheets is insufficient.
[0196] Examples I1B, I2B and I3B were batch annealed at a temperature of 500°C for 25200 seconds. The batch annealing resulted in a decrease in hardness compared to Examples I1A, I2A and I3A, which were not subjected to any annealing. However, the workability of Examples I1B, I2B and I3B is insufficient, since the batch annealing resulted in a decrease in Charpy energy. Also, the batch annealing resulted in the formation of cementite highly enriched in Mn.
[0197] Examples I1C, I2C, I3C, I6C and 7C were also subjected to batch annealing at a temperature of 600° C. for 25,200 seconds. As a result of the batch annealing, the hardness of these examples was reduced compared to Examples I1A, I2A, I3A, I6A and I7A, respectively, and further reduced compared to Examples I1B, I2B and I3B. However, the Charpy energy was reduced by 50 J / cm. 2 lower and batch annealing led to the formation of cementite that was highly enriched in Mn.
[0198] We then performed experiments by increasing the batch annealing temperature to 650°C above the Ae1 transformation point (Examples I1D, I2D, I3D, I6D and I7D). This higher batch annealing temperature resulted in an increase in the Charpy energy of the plates and a decrease in the average Mn content in cementite compared to Examples I1C, I2C, I3C, I6C and I7C, respectively.
[0199] Nevertheless, batch annealing at temperatures above Ae1 led to coarsening of the microstructure, with the ferrite grain size being larger than 3 μm.
[0200] The inventors further increased the batch annealing temperature to 680° C. (Examples I1E and I3E). This increase in batch annealing temperature resulted in a further increase in Charpy energy and a further decrease in the average Mn content in cementite. However, this increase in batch annealing temperature also resulted in a further undesirable increase in ferrite grain size.
[0201] Thus, these examples show that although batch annealing reduces the hardness of hot rolled steel sheets, the Charpy energy of hot rolled and batch annealed steel sheets is generally insufficient to ensure high workability of the steel sheets. Also, batch annealing undesirably produces cementite that is very rich in Mn. These examples further show that while increasing the batch annealing temperature can increase the Charpy energy and reduce the average Mn content in the cementite, the Charpy energy is often too low to meet the target value of 50 J / cm. 2annealing temperature remains lower, indicating that increasing the batch annealing temperature results in undesirable coarsening of the microstructure.
[0202] Although the specimen I3L was subjected to continuous annealing, the continuous annealing temperature was lower than 650° C. As a result, the softening due to the recovery of the microstructure was insufficient, so that the hardness of the specimen I3L was higher than 400 HV and the Charpy energy was insufficient.
[0203] Examples I1G and I3Q were annealed successively at annealing temperatures such that more than 30% austenite was produced during annealing. As a result, the fresh martensite fraction in the hot-rolled and annealed steel sheets was higher than 8%, so the hardness of these examples was higher than 400HV and their Charpy energy was higher than 50J / cm 2 Lower.
[0204] Examples I1F, I2H, I2J, I2K, I3H, I3M, I3O, I3P, I3J, I6K and I7K were subjected to continuous annealing under the conditions of the present invention. As a result, the hot rolled and annealed steel sheets had a rolling resistance of at least 50 J / cm 2 and a hardness of up to 400 HV. These hot rolled and annealed steel sheets therefore have sufficient cold rollability and workability. The microstructure of these examples is also such that the average ferrite grain size is smaller than 3 μm and the average Mn content in cementite is lower than 25%. These hot rolled steel sheets are therefore suitable for the production of cold rolled and heat treated steel sheets with high mechanical properties.
[0205] The microstructure of the hot-rolled and annealed steel sheet thus obtained was observed.
[0206] The microstructures of Examples I1E and I1F are shown in Figures 1 and 2, respectively.
[0207] As can be seen in these figures, the microstructure of steel I1F produced by continuous annealing according to the invention is much finer than the microstructure of steel I1E produced by batch annealing above Ae1.
[0208] These experiments demonstrate that, unlike batch annealing, continuous annealing according to the present invention results in a very fine microstructure.
[0209] The inventors have further carried out experiments to evaluate the final properties of cold rolled and heat treated steels produced from batch annealing below Ae1 or above Ae1 or subjected to a continuous annealing according to the invention before cold rolling.
[0210] In particular, steels I1, I2, I4, I5, I6 and I7 were cast into ingots. The ingots were heated to a temperature T reheat The steel was reheated at 400° C., scale was removed, and hot rolled at a temperature higher than Ar3 to obtain hot rolled steel.
[0211] Next, the hot-rolled steel sheet is heated to a temperature T coil and rolled it up.
[0212] The hot rolled steel sheets were then batch annealed or continuously annealed.
[0213] Next, the hot-rolled and annealed steel sheet is cold-rolled at a rolling reduction rate of 50%, annealed, and then cooled at a cooling rate of V c1 The alloy was subjected to various heat treatments, including cooling to room temperature at 400°C.
[0214] The yield strength, tensile strength, uniform elongation and hole expansion ratio of the cold rolled and heat treated steel sheets thus obtained were then measured.
[0215] The preparation conditions and measured properties are reported in Tables 4 and 5.
[0216] In these tables, T coil indicates the winding temperature, T A and t A are the batch or continuous annealing temperatures and times, HBA indicates batch annealing, ICA indicates continuous annealing according to the invention, T anneal is the annealing temperature, and t anneal is the annealing time, V C1is the cooling rate (or cooling conditions).
[0217] The measured properties reported in Tables 4 and 5 are yield strength YS, tensile strength TS, uniform elongation UE and hole expansion ratio HER.
[0218] In these tables, "nd" means "not determined." Underlined values are not according to the present invention.
[0219] [Table 4]
[0220] [Table 5]
[0221] The properties of the examples made of steel I4 are reported in FIG. 3 (UTS for tensile strength and UEl for uniform elongation).
[0222] In this figure, each curve corresponds to an annealing condition after hot rolling (black squares: batch annealing at 600°C for 300 min; white squares: continuous annealing at 700°C for 2 min), and each point on each curve reports the tensile strength and uniform elongation obtained at a particular annealing temperature, with it being understood that the higher the annealing temperature, the higher the tensile strength.
[0223] The results reported in FIG. 3 and Table 4 demonstrate that by practicing the continuous annealing of the present invention, it is possible to achieve an improved combination of tensile strength and elongation compared to batch annealing.
[0224] Steel sheets produced according to the invention can therefore be advantageously used for the manufacture of structural or safety parts of vehicles.
Claims
1. A method for producing a steel sheet, comprising the steps of: - in percent by weight 0.1%≦C≦0.4% 3.5%≦Mn≦8.0% 0.1%≦Si≦1.5% Al≦3% Mo≦0.5% Cr≦1% Nb≦0.1% Ti≦0.1% V≦0.2% B≦0.004% 0.002%≦N≦0.013% S≦0.003% P≦0.015% with the balance being iron and inevitable impurities resulting from smelting, to obtain a semi-finished steel product; the semi-finished steel product at a temperature T comprised between 1150°C and 1300°C reheat reheating the mixture to hot rolling the reheated semi-finished product at a temperature comprised between 800 ° C. and 1250 ° C., with a final rolling temperature T FRT is 800°C or more, thereby obtaining a hot-rolled steel sheet; The hot-rolled steel sheet is cooled at a cooling rate V between 1 ° C. / sec and 150 ° C. / sec. c1 The coiling temperature T is 650° C. or less. coil The hot-rolled steel sheet is cooled to a coiling temperature T coil Then, the process of winding the - T ICAmin ~T ICAmax The continuous annealing temperature T ICA A process of continuously annealing the hot-rolled steel sheet, comprising the steps of: ICAmin = 650 ° C., T ICAmax is the temperature at which 30% austenite is generated during heating, and the hot-rolled steel sheet is subjected to the continuous annealing temperature T ICA The continuous annealing time t is between 3 seconds and 3600 seconds. ICA and then cooling the hot-rolled steel sheet to room temperature, the hot-rolled steel sheet being cooled between 600 and 350 °C at an average cooling rate V of at least 1 °C / s. ICA thereby obtaining a hot rolled and annealed steel sheet. - cold rolling the hot rolled and annealed steel sheet with a cold rolling reduction ratio of 30-70%, thereby obtaining a cold rolled steel sheet. A method comprising:
2. The hot-rolled and annealed steel sheet has a surface fraction of - ferrite, the ferrite grains having an average size of up to 3 μm; - max. 30% austenite, - max. 8% fresh martensite, and - cementite with an average Mn content below 25% The method of claim 1 , having a tissue consisting of:
3. 3. The method according to claim 1 or 2, wherein the hot rolled and annealed steel sheet has a Vickers hardness lower than 400 HV.
4. The hot rolled and annealed steel sheet has a strength of at least 50 J / cm at 20°C. 2 The method according to any one of claims 1 to 3, wherein the Charpy energy is
5. The method according to any one of claims 1 to 4, further comprising pickling the hot rolled steel sheet between the coiling and the continuous annealing and / or after the continuous annealing.
6. The continuous annealing time t ICA The method according to any one of claims 1 to 5, wherein is comprised between 200 seconds and 3600 seconds.
7. After cold rolling, The cold-rolled steel sheet is subjected to an annealing temperature T anneal and - The cold-rolled steel sheet is annealed at a temperature T anneal The annealing time t is between 30 seconds and 10 minutes. anneal Hold for The method of any one of claims 1 to 6, further comprising:
8. The annealing temperature T anneal But, T ICAmin The method according to claim 7, which is included between Ae1 and Ae3.
9. The annealing temperature T anneal The method according to claim 7, wherein the temperature is comprised between Ae3 and 1000°C.
10. The cold-rolled steel sheet is annealed at a temperature T anneal from room temperature to a cooling rate V between 1 ° C. / sec and 70 ° C. / sec c2 10. The method according to claim 7, further comprising the step of cooling at 400 K to obtain a cold rolled and heat treated steel sheet.
11. The cold-rolled steel sheet is annealed at a temperature T anneal After holding at , the following successive steps: - The cold-rolled steel sheet is annealed at a temperature T anneal and a holding temperature T between 350°C and 550°C. H Cooling rate V from 1°C / sec to 70°C / sec c2 cooling with - a holding time t between 10 seconds and 500 seconds H The cold rolled steel sheet is held at a temperature T H and then - Holding the cold rolled steel plate at a temperature T H from room temperature to a cooling rate V between 1 ° C. / sec and 70 ° C. / sec c3 and cooling the steel sheet to obtain a cold-rolled and heat-treated steel sheet. The method of any one of claims 7 to 9, further comprising:
12. Tempering temperature T between 170 and 450 ° C. T The tempering time t is between 10 seconds and 1200 seconds. T 12. The method according to claim 10 or 11, further comprising the step of tempering the cold rolled and heat treated steel sheet during said step.
13. The method according to any one of claims 10 to 12, further comprising the step of coating the cold rolled and heat treated steel sheet with Zn or a Zn alloy, or Al or an Al alloy.
14. The following steps: The heated cold-rolled steel sheet is annealed at an annealing temperature T anneal From the quenching temperature QT included between Mf + 20 ° C. and Ms - 20 ° C., a cooling rate V high enough to avoid the formation of ferrite and pearlite during cooling c4 A process of hardening with The cold-rolled steel sheet is subjected to a carbon concentration temperature T which is between 350°C and 500°C from the quenching temperature QT. P The cold-rolled steel sheet is then reheated to a carbon concentration temperature T P The carbon concentration time t is between 3 seconds and 1000 seconds. P maintaining the temperature for a period of time; - cooling said cold rolled steel sheet to room temperature to obtain a cold rolled and heat treated steel sheet. The method of any one of claims 7 to 9, further comprising:
15. Annealing temperature T anneal However, the cold-rolled steel sheet has a surface fraction of between 10% and 45% ferrite, - austenite, and - maximum 0.3% cementite, the cementite grains having an average size, if any, smaller than 50 nm 15. The method of claim 14, wherein the tissue comprises:
16. Annealing temperature T anneal is higher than Ae3, and the cold-rolled steel sheet, during annealing, - austenite, and - maximum 0.3% cementite, the cementite grains having an average size, if any, smaller than 50 nm The method of claim 14 , having a tissue consisting of:
17. The cold-rolled steel sheet is heated to a carbon concentration temperature T P The method according to any one of claims 14 to 16, wherein after maintaining at 0.5° C., the cold rolled steel sheet is immediately cooled to room temperature.
18. Carbon concentration temperature T P The method according to any one of claims 14 to 16, wherein the cold rolled steel sheet is hot-dip galvanized in a bath during the period between holding the cold rolled steel sheet at 0° C. and cooling the cold rolled steel sheet to room temperature.
19. A cold rolled and heat treated steel sheet comprising, in weight percent: 0.1%≦C≦0.4% 3.5%≦Mn≦8.0% 0.1%≦Si≦1.5% Al≦3% Mo≦0.5% Cr≦1% Nb≦0.1% Ti≦0.1% V≦0.2% B≦0.004% 0.002%≦N≦0.013% S≦0.003% P≦0.015% and the balance being iron and unavoidable impurities resulting from smelting, and the cold-rolled steel plate is made from a steel having a composition comprising, in a surface fraction: - between 8 and 50% retained austenite, - maximum 80% intercritical ferrite, the ferrite grains having an average size, if any, of maximum 1.5 μm; - maximum 1% cementite, the cementite grains having an average size, if any, of less than 50 nm; - martensite and / or bainite A cold-rolled and heat-treated steel sheet having a structure consisting of
20. 20. The cold rolled and heat treated steel sheet according to claim 19, wherein the structure comprises a surface fraction of at least 10% intercritical ferrite.
21. The structure has a surface fraction of - between 8 and 50% retained austenite, - maximum 1% cementite, the cementite grains having an average size, if any, of less than 50 nm; - martensite and / or bainite 20. The cold rolled and heat treated steel sheet of claim 19, comprising:
22. The cold rolled and heat treated steel sheet according to any one of claims 19 to 21, wherein the martensite consists of tempered martensite and / or fresh martensite.
23. The structure has a surface fraction of - retained austenite having an average C content of at least 0.4% and an average Mn content of at least 1.3*Mn%, between 8% and 50%, Mn% indicating the average Mn content in the steel composition; - intercritical ferrite between 40% and 80%, - max. 15% martensite and / or bainite, and - maximum 0.3% cementite, the cementite grains having an average size, if any, of less than 50 nm 23. The cold rolled and heat treated steel sheet of claim 22, comprising:
24. The structure has a surface fraction of - retained austenite with an average C content of at least 0.4%, between 8% and 30%; between 70% and 92% martensite and / or bainite, and - maximum 1% cementite, the cementite grains having an average size, if any, of less than 50 nm 23. The cold rolled and heat treated steel sheet of claim 22, comprising:
25. The structure has a surface fraction of - max. 45% intercritical ferrite, - between 8% and 30% retained austenite, - carbon enriched martensite, - max. 8% fresh martensite, and - maximum 1% cementite, the cementite grains having an average size, if any, of less than 50 nm The cold rolled and heat treated steel sheet according to any one of claims 19 to 21.
26. The structure has a surface fraction of - intercritical ferrite between 10% and 45%, - between 8% and 30% retained austenite, - carbon enriched martensite, - max. 8% fresh martensite, and - maximum 0.3% cementite, the cementite grains having an average size, if any, of less than 50 nm 26. The cold rolled and heat treated steel sheet of claim 25, comprising:
27. The structure has a surface fraction of - between 8% and 30% retained austenite, - carbon enriched martensite, - max. 8% fresh martensite, and - maximum 1% cementite, the cementite grains having an average size, if any, of less than 50 nm 26. The cold rolled and heat treated steel sheet of claim 25, comprising: